EFFECT OF SHAPE OF SEDIMENT TRAP ON MEASUREMENT OF VERTICAL FLUX OF PARTICLES : PRELIMINARY RESULTS (14th Symposium on Polar Biology) - タグチ, サトル; サイトウ, ヒロアキ; カサイ, ヒロミ; TAGUCHI, Satoru; SAITO, Hiroaki; KASAI, Hiromi (National Institute of Polar Research, 1993)
P(論文) Settling experiments were conducted to study sinking characteristics of phytoplankton cells within sediment traps. Simulated traps with three different shapes, i.e. cylindrical and conical shape with 75 and 60 degree angles, were employed for laboratory experiments. Navicula sp. as non-motile species and Tetraselmis sp. as motile one were employed for the experiment. Vertical flux of phytoplankton cells was determined continuously with a fluorometer. The present study indicated that conical shape traps caused underestimation of flux and the degree of underestimation was a function of wall angles. The underestimation was accelerated for Tetraselmis sp. The present results may suggest that a deployment of conical shape traps with collectors at the bottom would seriously underestimate the vertical flux of particles in the ocean. departmental bulletin paper